ANALISIS FRAMING SEPUTAR INEWS SIANG RCTI SEGMEN “PILIHAN INDONESIA 2019” - Tubagus Muhammad Rayhan (Sekolah Tinggi Ilmu Komunikasi Inter Studi, 2020)
AbstractThis research is motivated by the existence of a democratic party in 2019, during those times the Seputar iNews Afternoon program made a special segment of political-specific news related to presidential candidates, vice presidential candidates and other political figures who were also part of important figures from the party period democracy. This study aims to find out how the framing of news or framing conducted by the Seputar iNews Siang program in the